Wood - Stafford, Fiona (Romanticism on the Net, 2023)
This essay attempts to see the wood and the trees by considering a selection of entries in RÊVE (Romantic Europe: The Virtual Exhibition). Living trees in the landscape are here included alongside products fashioned from timber to draw attention to the often-neglected dimensions of wooden items. While the sources of wood are rooted in particular places, objects made from timber are able to move and accrue meaning through use and association. The essay moves from the Selborne Yew, made famous in the Romantic period by Gilbert White, to a tea caddy derived from another contemporary literary celebrity, Yardley Oak, before considering travel boxes owned by Teresa Guiccioli and Byron and the implications of furniture fashions for the survival of rare arboreal species. The essay is concerned with different kinds of value, as influenced by commercial markets, fashion, quality, literary and historic association, and environmental concerns. It thus considers a Stradivari violin and an Ayrshire fiddle, a Mauchline ware binding and a literary monument set among living trees.